(untitled) (Research, Society and Development, 2022)
Over the last years much research has been carried out, especially after the influenza pandemic in 2009. It is known that many strains of influenza virus are widely spread in the global population causing seasonal outbreaks every year. Influenza leads to flu-like symptoms, which present favorable prognosis, since most patients completely recover from it within two to five days. Many new antiviral drugs have been developed in the last few years, but since the infection generally presents a mild course, symptom-based care is often enough. Influenza virus can undergo mutations through some mechanisms, like antigenic drift and antigenic shift. Alongside with its high infectivity such mechanisms probably have worked together to keep influenza infection viable through the years, despite all new drugs and preventive measures. This review aimed to bring the most relevant data about influenza obtained in the past years, including some historical aspects, pathophysiology, clinical findings, and diagnostic and therapeutic approach.